2021
DOI: 10.3389/fendo.2021.756336
|View full text |Cite
|
Sign up to set email alerts
|

Decreased DNA Repair Ability: A Mechanism for Low Early Embryonic Development Potential of Oocytes From Overweight Patients After Fertilization in IVF Cycles

Abstract: BackgroundWhether female BMI impacts the DNA repair ability in the oocytes after fertilization has not been investigated. The aim of this study is to assess the early embryo quality and reproductive outcomes of oocytes from overweight women when fertilized with sperm with varying degrees of DNA fragmentation.MethodsA total number of 1,612 patients undergoing fresh autologous in vitro fertilization (IVF) cycles was included. These patients were divided into two groups according to maternal body mass index (BMI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…However, in overweight/obese women, lower fertilization rate, cleavage rate, and high-quality embryo rate were observed in DFI≥30% cycles than in DFI<30% cycles. These findings are congruent with prior research on IVF cycles at our center ( 26 ), which revealed that in patients with normal weight, there was no statistically significant difference in the different levels of sperm fragmentation in terms of embryo quality and reproductive outcomes. However, in overweight patients, the high-fragmentation group had much lower rates of fertilization, blastocyst development, and high-quality blastocysts than the low-fragmentation group.…”
Section: Discussionsupporting
confidence: 91%
“…However, in overweight/obese women, lower fertilization rate, cleavage rate, and high-quality embryo rate were observed in DFI≥30% cycles than in DFI<30% cycles. These findings are congruent with prior research on IVF cycles at our center ( 26 ), which revealed that in patients with normal weight, there was no statistically significant difference in the different levels of sperm fragmentation in terms of embryo quality and reproductive outcomes. However, in overweight patients, the high-fragmentation group had much lower rates of fertilization, blastocyst development, and high-quality blastocysts than the low-fragmentation group.…”
Section: Discussionsupporting
confidence: 91%
“…Univariate linear regression analysis showed that fertilization rate was the only parameter among IVF outcomes significantly but weakly affected by HDS, while there was no correlation between fertilization rate and HDS after adjusting. This might be because the effect in univariate model was caused by female factors rather than HDS, given the small contribution of HDS to the equation in which the coefficient of determination (R 2 ) was 0.02 (data not shown) and the large and well-established role of female factors (such as advanced age, obesity, and poor ovarian reserve) in fertility [37][38][39]. Thus, the actually prognostic value of sperm HDS on fertilization was observed after adjusting.…”
Section: Discussionmentioning
confidence: 99%